60 - Morgan, Mihangel (Y Lolfa, 2017)
A collection of short stories by one of Wales's best known authors, comprising sixty stories portraying contemporary events which happen within one hour in a small Welsh town.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books